Highly Uniform Resistive Switching Performances Using Two-Dimensional Electron Gas at a Thin-Film Heterostructure for Conductive Bridge Random Access Memory - Kim, Sung Min; Kim, Hye Ju; Jung, Hae Jun; Kim, Seong Hwan; Park, Ji Yong; Seok, Tae Jun; Park, Tae Joo; Lee, Sang Woon (ACS Applied Materials and Interfaces, 2019)
This research demonstrates, for the first time, the development of highly uniform resistive switching devices with self-compliance current for conductive bridge random access memory using two-dimensional electron gas (2DEG) at the interface of an Al2O3/TiO2 thin-film heterostructure via atomic layer deposition (ALD). The cell is composed of Cu/Ti/Al2O3/TiO2, where Cu/Ti and Al2O3 overlayers are used as the active/buffer metals and solid electrolyte, respectively, and the 2DEG at the interface of Al2O3/TiO2 heterostructure, grown by the ALD process, is adopted as a bottom electrode. The Cu/Ti/Al2O3/TiO2 device shows reliable resistive switching characteristics with excellent uniformity under a repetitive voltage sweep (direct current sweep). Furthermore, it exhibits a cycle endurance over 107 cycles under short pulse switching. Remarkably, a reliable operation of multilevel data writing is realized up to 107 cycles. The data retention time is longer than 106 s at 85 °C. The uniform resistance switching characteristics are achieved via the formation of small (∼a few nm width) Cu filament with a short tunnel gap (<0.5 nm) owing to the 2DEG at the Al2O3/TiO2 interface. The performance and operation scheme of this device may be appropriate in neuromorphic applications.
Keywords: Compliance current; Data retention time; Random access memory; Resistance switching; Resistive switching; Resistive switching devices; Short-pulse switching; Two-dimensional electron gas (2DEG); atomic layer deposition; conductive bridge random access memory; oxide heterostructure; thin film; two-dimensional electron gas